METABOLIC PROFILE OF COMMERCIAL BIRDS USING DIRECT METHODS - Flórez, Jancy Darly (2013)
This study measured and compared the levels of low and high-density lipoprotein cholesterol in broilers and laying hens to determine the type of lipoprotein in higher concentration, using an analytical method that cannot be affected by high concentrations of triglycerides. Blood samples were collected in 30 broilers (Cobb 500) of 35-day-old and in 40 laying hens (Hy-Line W-36) 26 weeks old. Cholesterol levels of low and high density lipoproteins were measured by direct methods based on detergents and N,N-Bis(4-sulfobutyl)-m-toluidine. The results showed that high density lipoprotein cholesterol was more abundant in both broilers (93.1 ± 16 vs. 52.2 ± 9.1 mg/dL) and laying hens (61.7 ± 15.4 vs. 49.1 ± 12.6 mg/dL). It was concluded that using direct methods based on detergents and N,N-Bis (4- sulfobutyl)-m-toluidine, the high density lipoprotein is the metabolic pattern of lipids in commercial poultry.